KEMAMPUAN LITERASI NUMERASI MATEMATIS SISWA DALAM MEMECAHKAN MASALAH BARISAN DAN DERET ARITMATIKA - Nisa, Novi Darojatun; Ramlah, Ramlah (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2023)
This research aim to describe students’ numeracy literacy skills in solving mathematics problems in the form of story problems. The students involved were class X students at one of 36 high schools in Karawang district, then selected 3 students with high, medium, and low numeracy literacy skills. The method used is a case study research method with a qualitative descriptive approach. The data collection technique usedin this survey is a two  dimensional description test of arithmetic rows and rows, documentation, and interviews. The data analysis technique is in the formof an aveage percentage for each indicator of numeracy literacy ability, availability of subject to be intervewed, subject  answer and conclusions. The results of the  study show that the subject with high numbering numeracy literacy is capable of  solving problems using  symbols and numbers, able to analyze the information presented, and able to interpret the result of the analysis to draw the conclusion correctly, where as the subjects with the literacy of categorical numeration are not  capable of interpreting the results of analysis, and subject with low category numerational literacy does not meet the three indicators of numerational literacy, this is because the student isnot  accustomed to working on the story. It was concluded that the numerical literacy of the entire student was categorized quite well.